Tissue-specific histone modification and transcription factor binding in alpha globin gene expression. - De Gobbi, M; Anguita, E; Hughes, J; Sloane-Stanley, J; Sharpe, J; Koch, C; Dunham, I; Gibbons, R; Wood, W; Higgs, D (2007)
To address the mechanism by which the human globin genes are activated during erythropoiesis, we have used a tiled microarray to analyze the pattern of transcription factor binding and associated histone modifications across the telomeric region of human chromosome 16 in primary erythroid and nonerythroid cells. This 220-kb region includes the alpha globin genes and 9 widely expressed genes flanking the alpha globin locus. This un-biased, comprehensive analysis of transcription factor binding and histone modifications (acetylation and methylation) described here not only identified all known cis-acting regulatory elements in the human alpha globin cluster but also demonstrated that there are no additional erythroid-specific regulatory elements in the 220-kb region tested. In addition, the pattern of histone modification distinguished promoter elements from potential enhancer elements across this region. Finally, comparison of the human and mouse orthologous regions in a unique mouse model, with both regions coexpressed in the same animal, showed significant differences that may explain how these 2 clusters are regulated differently in vivo.